Problematika Pengaturan Restorative Justice terhadap Tindak Pidana Kekerasan Seksual dalam Sistem Peradilan Pidana di Indonesia - Haliza Layla Tsabita; Apriliani Kusumawati (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2026)
Regulatory inconsistencies pose a barrier to the implementation of restorative justice in Indonesia, particularly in the handling of sexual violence cases. This issue arises because Article 5 of Police Regulation No. 8/2021 does not exclude sexual violence crimes from the restorative justice mechanism, while Article 21 of Law No. 12/2022 explicitly prohibits the resolution of cases outside the judicial process. This study aims to analyze the normative limitations of applying restorative justice in sexual violence cases and to identify the implications of regulatory disharmony on legal certainty. This study employs a normative legal methodology, drawing on legislative, conceptual, and case-based approaches. The results of the study indicate that this regulatory disharmony leads to multiple interpretations, weakens legal certainty, and disrupts the coherence of restorative justice implementation within the criminal justice system; therefore, regulatory harmonization is necessary through the establishment of an integrated legal framework oriented toward victim protection.